Effect of Formant Frequency Spacing on Perceived Gender in Pre-Pubertal Children's Voices - Cartei, Valentina (Public Library of Science, 2013)
BACKGROUND: It is usually possible to identify the sex of a pre-pubertal child from their voice, despite the absence of sex differences in fundamental frequency at these ages. While it has been suggested that the overall spacing between formants (formant frequency spacing - ΔF) is a key component of the expression and perception of sex in children's voices, the effect of its continuous variation on sex and gender attribution has not yet been investigated. METHODOLOGY/PRINCIPAL FINDINGS: In the present study we manipulated voice ΔF of eight year olds (two boys and two girls) along continua covering the observed variation of this parameter in pre-pubertal voices, and assessed the effect of this variation on adult ratings of speakers' sex and gender in two separate experiments. In the first experiment (sex identification) adults were asked to categorise the voice as either male or female. The resulting identification function exhibited a gradual slope from male to female voice categories. In the second experiment (gender rating), adults rated the voices on a continuum from “masculine boy” to “feminine girl”, gradually decreasing their masculinity ratings as ΔF increased. CONCLUSIONS/SIGNIFICANCE: These results indicate that the role of ΔF in voice gender perception, which has been reported in adult voices, extends to pre-pubertal children's voices: variation in ΔF not only affects the perceived sex, but also the perceived masculinity or femininity of the speaker. We discuss the implications of these observations for the expression and perception of gender in children's voices given the absence of anatomical dimorphism in overall vocal tract length before puberty.